SOSIALISASI POTENSI LOKAL ACEH BARAT MELALUI PEMANFAATAN ALGA COKELAT (Sargassum sp) KEPADA MASYARAKAT PESISIR DI PANTAI LHOK BUBON ACEH BARAT - Mohamad Gazali; Zuriat Zuriat (Jurnal Marine Kreatif, 2019)
Indonesia is the biggest archipelago state that have high marine biodiversity. One of the marine biodiversity that have bright prospect in the future are marine macroalgae. Marine macroalgae have distributed widely in the coastal area of Indonesia especially West South Aceh. Marine macroalga have distributed in the West South Aceh. Marine macroalgae are consist of three classes namely Rhodophyta, Phaeophyta dan Chlorophyta classes. One of the marine macroalgae that have important economical value is brown algae (Sargassum sp). However, the utilization of brown algae (Sargassum sp) has not yet optimal. It is caused by lack of knowledge and skill related marine macroalgae processing. Therefore, the researcher has conducted the activity of empowering community at Lhok Bubon Coastal area. The conducting method of the activity of empowering community including survey of brown alga’s site, the socialization of brown alga utilization and forming the coastal community group. The result that reached in conducting empowering community was the enhanching of knowledge and skill of coastal community. The conducting of empowering community were acknowledged by coastal community of Lhok Bubon. Their hope are how to process the brown alga in order to give value added for local community prosperity.